Impact of delirium on patients hospitalized for myocardial infarction: A propensity score analysis of the National Inpatient Sample. Issue 7 (20th July 2018) - Abdullah, Abdullah; Eigbire, George; Salama, Amr; Wahab, Abdul; Awadalla, Mohanad; Hoefen, Ryan; Alweis, Richard
Abstract : Background: Delirium is associated with worse outcomes in critically ill patients. In the subset of patients with myocardial infarction (MI), the impact on clinical outcomes of delirium is not as well elucidated. Hypothesis: Delirium is associated with increased mortality in patients hospitalized for MI. Methods: The study used data from the National Inpatient Sample 2012 to 2014, Healthcare Cost and Utilization Project. We included discharges associated with the primary diagnosis of MI using the relevant International Classification of Diseases, Ninth Revision, Clinical Modification codes. The outcome was inpatient mortality between the delirium group and propensity score–matched controls without delirium. Results: The study included 1 330 020 weighted discharges with MI as the principal diagnosis. Within this cohort, 18 685 discharges (1.4%) had delirium. Delirium was associated with older age, lower rates of percutaneous coronary intervention, and increased comorbid conditions. The delirium group had higher mortality (10.5% vs 2.6%, P < 0.001). Propensity score–matching analysis showed increased mortality in the delirium group (10.5% vs 7.6%, relative risk: 1.39 [95% confidence interval: 1.2–1.6, P < 0.001) using nearest neighbor 1:1 matching. Conclusions: In individuals with MI, delirium was associated with increased inpatient mortality.